A Henry Wadsworth Longfellow companion - Gale, Robert L., 1919-2020 (Greenwood Press, 2003)
Best remembered today as the author of The Song of Hiawatha, Longfellow continues to be one of the most popular poets in American literary history. This book is a guide to his life and writings. A brief introductory essay overviews Longfellow's life and accomplishments. A chronology then summarizes the chief events in his career. Hundreds of alphabetically arranged entries follow, discussing individual poems, his other writings, his family members and professional associates, and topics related to his life and literary achievements. Entries list works for further reading, and the volume closes.